THE IMPACT OF GOOD CORPORATE GOVERNANCE ON ESG PERFORMANCE: EVIDENCE FROM INDONESIAN LISTED COMPANIES - Hendri Bin Muhammad Nur; Muhammad Azril (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2024)
This study examines the impact of Good Corporate Governance (GCG) on Environmental, Social, and Governance (ESG) performance in Indonesian listed companies. Using data from 100 firms on the Indonesia Stock Exchange (2020–2022), collected through annual and sustainability reports as well as third-party ESG ratings, regression and correlation analyses demonstrate a strong positive relationship between governance and sustainability outcomes. Firms with stronger GCG—measured by board structure, transparency, and accountability—show significantly higher ESG scores, with a one-point improvement in governance corresponding to a 0.45-point increase in ESG performance. Sectoral analysis reveals that manufacturing firms outperform financial institutions, while board diversity, particularly gender representation, further enhances sustainability initiatives. These findings reinforce stakeholder theory, indicating that governance mechanisms promote inclusivity and long-term value creation. The study contributes empirical evidence from an emerging economy, highlighting how regulatory frameworks and market pressures strengthen the governance–sustainability nexus. Overall, GCG is shown to be a strategic driver that not only improves ESG performance but also enhances competitiveness, investor confidence, and sustainable growth in Indonesia’s corporate sector.